Testing the minimum approach distance guidelines for incubating Royal penguins Eudyptes schlegeli - Holmes, ND; Giese, M; Kriwoken, LK (2005)
Minimum approach distance guidelines are common tools to maintain a buffer between breeding seabirds and human activity, with the goal of mitigating potentially harmful impacts from these interactions. We employed an experimental design to measure the heart rate and behaviour of Royal penguins on Macquarie Island, Australia, in response to a single pedestrian visit using the current recommended approach distance of 5 m for visitors. Penguins showed increased heart rate (1.23 times average resting heart rate) and vigilance (six-fold increase), suggested to be a precursor to a flight or fight response, however, no penguins fled their nests. These responses were significantly greater than observed during Subantarctic skua overflights, suggesting incubating Royal penguins viewed a single pedestrian at 5 m as a greater threat than a predator overflight. Single persons using the current minimum approach guideline when visiting incubating Royal penguins appear unlikely to elicit responses considered greater than minor or transitory, consistent with activities that are considered acceptable by current management arrangements on Macquarie Island. However, applying this guideline requires caution because the cumulative impacts of visitation are unknown and greater responses may occur with larger group sizes or during different breeding phases. We consider minimum approach distance guidelines should be based on the separation distance necessary to allow animals to undertake normal activity, rather than on the distance people can approach wildlife before the animals flee. Â© 2005 Elsevier Ltd. All rights reserved.